Health concerns and health-risk behaviors among school-aged children in Saudi Arabia - Ali Saad R. Alsubaie (Journal of Family Medicine and Primary Care)
Childhood and adolescence are profoundly important for the public health future. Children and adolescents experience rapid physical, physiological, and behavioral changes. In addition, there is substantial evidence that the promotion and protection of childhood health are essential to sustainable public health and social and economic development. This review explored research relevant to children and adolescent health-related behaviors to identify key behaviors and behavioral factors for targeting health promotion interventions. We examine what is currently known about health-related behaviors including dietary behaviors, physical activity, smoking, sexual behaviors, violence, and mental health and the health needs of the importance of strengthening children and adolescent health services to meet their needs. The review was conducted using electronic databases of PubMed and Google Scholar and official websites. Most of the studies found were cross-sectional, and they dealt with specific health behaviors. In general, Saudi children and adolescents engage in a wide range of risky behaviors at an alarming rate, including low physical activity, poor dietary behaviors, a high rate of overweight and obesity, smoking cigarettes, and engaging in violent behaviors. However, there is limited information on the magnitude of health-related problems and risky behaviors among children and adolescents in Saudi Arabia. It is imperative to note that similar to adolescents and children around the world, Saudi’s young population is at risk of a myriad of communicable and noncommunicable diseases owing to the high prevalence of various health risk behaviors. Although school health services need improvement, we first need more detailed and systematic national data on child and adolescent health-related behaviors in Saudi Arabia.